Peran Komunikasi Penyidik Polri dalam Implementasi UU No. 20 Tahun 2001 untuk Pencegahan Korupsi - Perdana, Cuanda Mitra; Sazali, Hasan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study aims to explore the role of communication by Indonesian National Police (Polri) investigators in the implementation of Law No. 20 of 2001 on the Eradication of Corruption Crimes (Corruption Law), with a focus on efforts to prevent corruption. The research method used is library research with a qualitative normative legal approach, examining relevant literature and documents, such as books, journals, regulations, and articles discussing communication aspects in law enforcement and corruption prevention efforts. The data analysis technique applied is descriptive qualitative analysis. The findings of this study indicate that communication by Polri investigators plays a crucial role in various stages of investigation, including ensuring transparency, protecting the rights of suspects, and coordinating with related agencies. Effective communication can drive the achievement of corruption prevention goals through the collection of accurate evidence, strict supervision, and legal education and socialization to the public. Furthermore, this study highlights the importance of enhancing the capacity of law enforcement officers and internal oversight to prevent corruption practices within the Polri institution. The results of this research are expected to see the effectiveness of communication in the eradication and prevention of corruption.